Semiotics of the 20th century. - Ivanov, Vyacheslav V. (Sign Systems Studies, 2008)
Semiotic and linguistic studies of the 20th century have been important mostly in two senses — (1) they have opened a road for comparative research on the origin and development of language and other systems of signs adding a new dimension to the history of culture; (2) they have shown a possibility of uniting different fields of humanities around semiotics suggesting a way to trespass separation and atomisation of different trends in investigating culture. In the 21st century one may hope for closer integration of semiotics and exact and natural sciences. The points of intersection with the mathematical logic, computer science and information theory that already exist might lead to restructuring theoretical semiotics making it a coherent and methodologically rigid discipline. At the same time, the continuation of neurosemiotic studies promises a breakthrough in understanding those parts of the work of the brain that are most intimately connected to culture. From this point of view semiotics may play an outstanding role in the synthesis of biological science and humanities. In my mind that makes it a particularly important field of future research.